Didaktik der slawischen Sprachen Beiträge zum 1. Arbeitskreis in Berlin (12.-14.9.2016) - Bergmann, Anka; Caspers, Olga; Stadler, Wolfgang (Innsbrucker Beiträge zur Fachdidaktik, 2018)
In September 2016, the working group "Subject-Specific Pedagogy of Slavic Languages" organised an opening meeting which took place at the Department of Slavic Studies at the Humboldt-Universität in Berlin. The initiators Anka Bergmann, Olga Caspers (Berlin) and Wolfgang Stadler (Innsbruck) established this forum with the intention of improving academic exchange among colleagues and furthering discourse with the reference discipline. The forum provides scholars with the opportunity to benefit from this dialogue, to get involved in theoretical and practice-based discussions and to advance their research on the basis of individual talks and group discussions. Owing to the works published in the series "Innsbruck Contributions to Subject-Specific Language Education", the research field "Subject-specific Pedagogy of Slavic Languages" achieves the status it deserves in the academic community. The present volume contains twelve papers by thirteen German and Austrian experts presenting insights into their empirical and intercultural research, focusing on issues of Russian as a heritage language and suggesting practice-oriented approaches to the teaching and learning of a Slavic language. - Im September 2016 fand am Institut für Slawistik der Humboldt-Universität zu Berlin das Auftakttreffen des Arbeitskreises "Didaktik der slawischen Sprachen" statt, an dem FachdidaktikkollegInnen aus Deutschland und Österreich teilnahmen, die sich zwischen übergreifend-fremdsprachendidaktischen und slawistisch-fachwissenschaftlichen Kontexten bewegen. Die InitiatorInnen Anka Bergmann, Olga Caspers (Berlin) und Wolfgang Stadler (Innsbruck) haben dieses Forum mit der Absicht ins Leben gerufen, den Austausch von fachdidaktischer Forschung in den slawischen Sprachen und die Diskussion mit der Bezugsdisziplin Slawistik zu verbessern. WissenschaftlerInnen profitieren vom kollektiven Fachgespräch, dem forschungsgeleiteten, theorie- und praxisgestützten Diskurs und entwickeln ihn auf der Grundlage individueller Vorträge und gemeinsamer Gespräche weiter. Mit der Publikation in der Reihe "Innsbrucker Beiträge zur Fachdidaktik" wird somit das Arbeitsgebiet "Didaktik der slawischen Sprachen" in der wissenschaftlichen Öffentlichkeit auch deutlich sichtbar(er). Der vorliegende Band enthält zwölf Aufsätze von dreizehn deutschen und österreichischen FachdidaktikerInnen zu Themen der empirischen, interkulturellen, herkunftssprachlichen und praxisorientierten Fachdidaktik.